PENGARUH CITRA MEREK DAN KEPERCAYAAN TERHADAP MINAT BELI KORAN HARIAN SUARA MERDEKA SEMARANG - Gina Devi Avianti, 15.05.51.0017; Marlien, Ra (Students' Journal of Economic and Management, 2019)
This study aims to test and analyze the influence of brand image and trust in buying interest in the Suara Merdeka daily newspaper Semarang. The population in this study were consumers who bought the Suara Merdeka daily newspaper. Because the population was very large, this study took a sample of 101 respondents. The sampling technique in this study used purposive sampling, namely the technique of determining samples with certain criteria, namely those who bought the daily newspaper Suara Merdeka. The data used in this study is primary data, with a questionnaire as a research instrument. The analytical tool used is multiple linear regression, validity test, reliability test, F test, coefficient of determination test (R²), and t test, which is then processed by calculation of SPSS (Statistical Product and Solutions) version 19. The results showed that brand image and trust has a positive and significant effect on buying interest.